Cadherins Interact With Synaptic Organizers to Promote Synaptic Differentiation - Yamagata, Masahito; Duan, Xin; Sanes, Joshua R. (Frontiers in Molecular Neuroscience, 2018)
Classical cadherins, a set of ~20 related recognition and signaling molecules, have been implicated in many aspects of neural development, including the formation and remodeling of synapses. Mechanisms underlying some of these steps have been studied by expressing N-cadherin (cdh2), a Type 1 cadherin, in heterologous cells, but analysis is complicated because widely used lines express cdh2 endogenously. We used CRISPR-mediated gene editing to generate a HEK293 variant lacking Cdh2, then compared the behavior of rodent cortical and hippocampal neurons co-cultured with parental, cdh2 mutant and cdh2-rescued 293 lines. The comparison demonstrated that Cdh2 promotes neurite branching and that it is required for three synaptic organizers, neurologin1 (NLGL1), leucine-rich repeat transmembrane protein 2 (LRRtm2), and Cell Adhesion Molecule 1 (Cadm1/SynCAM) to stimulate presynaptic differentiation, assayed by clustering of synaptic vesicles at sites of neurite-293 cell contact. Similarly, Cdh2 is required for a presynaptic organizing molecule, Neurexin1, to promote postsynaptic differentiation in dendrites. We also show that another Type I cadherin, Cdh4, and a Type II cadherin, Cdh6, can substitute for Cdh2 in these assays. Finally, we provide evidence that the effects of cadherins require homophilic interactions between neurites and the heterologous cells. Together, these results indicate that classical cadherins act together with synaptic organizers to promote synaptic differentiation, perhaps in part by strengthening the intracellular adhesion required for the organizers to act efficiently. We propose that cadherins promote high affinity contacts between appropriate partners, which then enable synaptic differentiation.